Epistemologi Fatwa tentang Politik Uang di Indonesia - Jefry Tarantang; A. Hafiz Anshary; Sukarni; Fahmi Hamdi; Athoillah Islamy (IAIN Langsa, 2022)
This study intends to identify the epistemology of the Fatwa of the Indonesian Ulema Council on the monasticism of money politic. Qualitative research in the form of literature studies uses a normative-philosophical approach. The primary data of this study is in the form of a document of the Ijtima' Ulama Decree of the Indonesian Fatwa Commission in 2018. Secondary data uses a variety of correlative scientific literature with a focus on discussion. The theory of idealism and the realism of Islamic law became the theory of analysis of this research. Data collection through documentation. Meanwhile, data analysis goes through the stages of data reduction, data presentation, and data verification. This research shows the epistemological construction of the fatwa of the Indonesian Ulema Council on the political monastery of money not only based on the idealistic-normative-deductive epistemology of Islamic law, but also emphasizes the aspects of Islamic legal realism in the form of considerations about the effectiveness of the fatwa in the midst of community life. The theoretical implications of this study show that the provisions of Islamic law (fatwa) related to the prohibition of money politics require considerations of legal formulations that do not only refer to normative idealism of law, but also legal realism. The limitations of this study have not identified the method of interpretation of the Indonesian Ulema Council on various theological foundations of monasticism of money politics.